Constructive Play on Numeracy Skills in Elementary School - Reflina Sinaga; Ester Julinda Simarmata (BIRCU, 2020)
The research objective in this paper is to find out how constructive games are on numeracy skills in elementary schools. This research is expected to contribute to schools and enrich the results of existing research and can provide an overview of how constructive play is on numeracy skills in elementary schools. This research is a type of classroom action research. This type of classroom action research used in this research is collaborative, namely that the person who will take the action must also be involved in the research process. In this activity, all who are involved in this research are full involved in the process of planning, acting, observing, and reflecting.